Optimal Impartial Correspondences - Cembrano, Javier; Fischer, Felix; Klimm, Max (arXiv.org, 2023)
We study mechanisms that select a subset of the vertex set of a directed graph in order to maximize the minimum indegree of any selected vertex, subject to an impartiality constraint that the selection of a particular vertex is independent of the outgoing edges of that vertex. For graphs with maximum outdegree \(d\), we give a mechanism that selects at most \(d+1\) vertices and only selects vertices whose indegree is at least the maximum indegree in the graph minus one. We then show that this is best possible in the sense that no impartial mechanism can only select vertices with maximum degree, even without any restriction on the number of selected vertices. We finally obtain the following trade-off between the maximum number of vertices selected and the minimum indegree of any selected vertex: when selecting at most~\(k\) vertices out of \(n\), it is possible to only select vertices whose indegree is at least the maximum indegree minus \(\lfloor(n-2)/(k-1)\rfloor+1\).